1979
DOI: 10.3177/jnsv.25.427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low protein diets on free amino acids in plasma of young men: Effect of wheat gluten diet.

Abstract: SummaryStudies were made on alterations in plasma amino acids in young men fed a diet containing graded levels of wheat gluten. After one week on a standard diet containing 200mgN/kg of mixed protein (animal protein content 45%), 38 young men were given a wheat gluten diet containing 170, 100, 60, 30, 15 or zero mgN/kg for 2 weeks. Blood samples measuring plasma free amino acids were taken before breakfast at the end of the periods on a standard diet and an experimental diet. In subjects on diets containing 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Nevertheless, we found that the lysine concentrations in the plasma, muscle and liver of adult rats given these proteins were almost normal irrespective of the dietary protein level. These findings in adult rats accorded with results observed in the plasma of young men given graded levels of wheat gluten (3), and possible explanations of these results have been discussed in detail in a previous report (3). Thus, the responses of free lysine in the plasma and tissues to dietary gluten differ in adult and growing animals, and in adults, the free lysine levels in the plasma and tissues do not always reflect the degree of lysine deficiency of the diet.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Nevertheless, we found that the lysine concentrations in the plasma, muscle and liver of adult rats given these proteins were almost normal irrespective of the dietary protein level. These findings in adult rats accorded with results observed in the plasma of young men given graded levels of wheat gluten (3), and possible explanations of these results have been discussed in detail in a previous report (3). Thus, the responses of free lysine in the plasma and tissues to dietary gluten differ in adult and growing animals, and in adults, the free lysine levels in the plasma and tissues do not always reflect the degree of lysine deficiency of the diet.…”
Section: Discussionsupporting
confidence: 87%
“…The reliability of the E/N ratio as an index of the protein nutritional status has been demonstrated in children (18), growing rats (10) and young men (1,3). In this study on adult rats, the E/N ratio in the plasma showed a significant correlation with the dietary protein level and the slope of the regression line obtained also reflected the quality of the protein.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…Moreover, passive equilibration of the urea pool is normally complete after about 1 day, whereas urinary N excretion continues to decrease for up to a week during the adaptation to protein deficiency 59 . Changes in the free glutamine pool can cause rapid changes in N balance 61 , 62 (although not by as much as has been speculated 63 ), but humans appear not to reduce their NEAA pool in response to a protein‐deficient diet 64 . We may conclude that adaption to protein deficiency indeed involves a delayed reduction in the rate of amino acid catabolism.…”
Section: Labile Proteinmentioning
confidence: 99%